Corporate fraud handbook : prevention and detection - Wells, Joseph T. (Hoboken, N.J. : John Wiley & Sons, 2007)
Now in a second edition, Corporate Fraud Handbook provides an insider's look into the most prevalent fraud schemes used by employers, owners, managers, and executives. Each scheme is illustrated with real-life case studies submitted to the Association of Certified Fraud Examiners (ACFE) by certified fraud examiners who aided in the case resolutions.
Includes bibliographical references (p. 429-436) and index.
oif 17/03/15
Loan
Keywords: Fraud; Corporations -- Corrupt practices; Fraud investigation; Fraud -- Prevention